Isolated Intradural Prepontine Chordoma Presenting with Imaging Features of Epidermoid Cyst - Alijani, Babak; Namin, Ahmad Kheiri (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2022)
Chordoma is an erratic aggressive tumor of the brain that typically involves the clivus. The majority of the clivus chordomas reside in the extradural space. Here, we report a unique case of chordoma arising from the prepontine intradural space without bony involvement and presenting with radiological features typical of an epidermoid cyst on magnetic resonance imaging.
Keywords: cyst; epidermoid; chordoma; clivus; differential diagnosis; MRI; prepontine